The media go-along: Researching mobilities with media at hand - Jørgensen, Kristian Møller (MedieKultur: Journal of media and communication research, 2016)
This article contributes methodologically and theoretically to Christine Hine’s call for a mobilities oriented internet ethnography. First, a ‘media go-along’, combining interviews and observations of a personal communication service at hand, is developed. Research participants give verbal and visual tours, framed by the researcher’s discursively constituted invitations for orientation. Then, a theoretical framework integrating an analysis of media environment mobilities is developed. From research material on hook-up and dating apps targeting non-heterosexual men, it is shown how 1) research participants’ navigation is materially contingent upon the medium and subject to momentary purposes and styles, 2) researcher presence and access must regularly be re-inscribed discursively, and 3) mobile media analysis, based on the media go-along’s representations of verbal, material, affective, and kinetic aspects of social interaction, is useful in the analysis of socially-conditioned access to, and production of, single media practice and experience.